Structural and functional characterization of sulfurtransferase from Frondihabitans sp. PAMC28461. - Hackwon Do; Dieu Linh Nguyen; Yong-Yoon Ahn; Yewon Nam; YoonJi Kang; HoeJung Oh; Jisub Hwang; Se Jong Han; Kitae Kim; Jun Hyuck Lee (PLoS ONE, 2024)
Sulfurtransferases transfer of sulfur atoms from thiols to acceptors like cyanide. They are categorized as thiosulfate sulfurtransferases (TSTs) and 3-mercaptopyruvate sulfurtransferases (MSTs). TSTs transfer sulfur from thiosulfate to cyanide, producing thiocyanate. MSTs transfer sulfur from 3-mercaptopyruvate to cyanide, yielding pyruvate and thiocyanate. The present study aimed to isolate and characterize the sulfurtransferase FrST from Frondihabitans sp. PAMC28461 using biochemical and structural analyses. FrST exists as a dimer and can be classified as a TST rather than an MST according to sequence-based clustering and enzyme activity. Furthermore, the discovery of activity over a wide temperature range and the broad substrate specificity exhibited by FrST suggest promising prospects for its utilization in industrial applications, such as the detoxification of cyanide.